2015
DOI: 10.3402/ijch.v74.27669
|View full text |Cite
|
Sign up to set email alerts
|

“We are like lemmings”: making sense of the cultural meaning(s) of suicide among the indigenous Sami in Sweden

Abstract: BackgroundSuicide is a widespread problem among indigenous people residing in the circumpolar Arctic. Though the situation among the indigenous Sami in northern Scandinavia is better than among some other indigenous people, suicide is still regarded as a major public health issue. To adapt prevention strategies that are culturally attuned one must understand how suicide is understood within context. That is, the cultural meaning(s) of suicide.ObjectiveTo explore and make sense of the cultural meaning(s) of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…Qualitative methodology is well suited to consider cultural and contextual issues in relation to suicide [14,15,19]. Focus group discussions (FGDs) have previously been used to investigate cultural understandings of suicide in specific populations [20,21], also among Indigenous peoples in the Arctic [22][23][24]. The study by Stoor et al [24] explored the cultural meanings of suicide among Sámi in Sweden and found that it was understood to be connected to difficulties of maintaining Sámi identity, i.e.…”
Section: Culture and Context In Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative methodology is well suited to consider cultural and contextual issues in relation to suicide [14,15,19]. Focus group discussions (FGDs) have previously been used to investigate cultural understandings of suicide in specific populations [20,21], also among Indigenous peoples in the Arctic [22][23][24]. The study by Stoor et al [24] explored the cultural meanings of suicide among Sámi in Sweden and found that it was understood to be connected to difficulties of maintaining Sámi identity, i.e.…”
Section: Culture and Context In Suicidementioning
confidence: 99%
“…Focus group discussions (FGDs) have previously been used to investigate cultural understandings of suicide in specific populations [20,21], also among Indigenous peoples in the Arctic [22][23][24]. The study by Stoor et al [24] explored the cultural meanings of suicide among Sámi in Sweden and found that it was understood to be connected to difficulties of maintaining Sámi identity, i.e. to maintain the traditional reindeer herding culture in face of difficulties posed by modern society and lack of (Sámi) political power.…”
Section: Culture and Context In Suicidementioning
confidence: 99%
“…Fourthly, men might run a higher risk, as they are more often directly responsible for the herding business in the family. Fifthly, the focus on independence and autonomy in male gender roles is perhaps leading males into a gender trap, where they cannot ask for help or solve their personal problems [9,10,20]. This is especially worrisome as the only study on mental health in the reindeer herding population in Sweden found that almost 40% of reindeer herding men reported clinically relevant (mild to severe) levels of anxiety symptoms, as measured with the Hospital Anxiety Depression Scale (HADS) [21].…”
Section: The Roles Of Sex and Gendermentioning
confidence: 99%
“…Also, sociocultural dynamics such as traditional "hardening" up-bringing styles, lateral violence and multiplex relations among Sámi are being discussed in the Sámi discourse on suicide. The small, tight-knit Sámi community may result in many bereaved by each case of suicide [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation